Effect of thermal popping treatment on Toluqueño creole popcorn maize (Zea mays L.): Changes in physical and structural properties (Agro Productividad, 2025)
Objective: To assess the effect of popping thermal treatment on the physical and structural properties of Toluqueño creole popcorn maize (Zea mays L.)Design/methodology/approach: Toluqueño creole maize and commercial (Zea mays L.) used as a control, were subjected to three popping treatments: hot oil, hot air, and microwave. Popping yield, textural properties, and structural features were determined.Results: The results showed that the treatment by hot air in commercial maize showed the highest pop yield (71.88%), while the microwave treatment was the best for Toluqueño maize (12.93%). The best textural characteristics for both types of maize were obtained after applying the hot air treatment, resulting in soft, low rubbing, and good chewing popcorns. The microstructural analysis on raw Toluqueño maize showed an intergranular space, which was related to a less compaction grade and consequently less hardness, meanwhile, the microwave popcorns showed the lowest gelatinization degree.Limitations on study/implications: High resolution and improved methodologies to observe the starch grain and components distribution could have resulted in a better description of the effect of thermal treatment on the corn grains.Findings/conclusions: Hot air treatment was the best process to obtain a good quality popcorn. The popping yield was related to humidity, hardness, grain shape, intergranular space, and the popping process.